Coastal Geoelectrical Survey at the Ancient Harbor of Lechaion (Greece) - Alexopoulos, J.D.; Dilalos, S.; Mitsika, G.S. (Bulletin of the Geological Society of Greece, 2019)
The study area is located at coastal area of the Ancient Harbor of Lechaion, at the area of the outer harbor moles (Figs. 1- 2), in order to investigate a possible extension of the existing ancient settlements. It is located on the southeastern coast of the Corinthian Gulf, 3km to the west of the modern city of Corinth, Greece. The construction of the Ancient Harbor dates to the 6th-7th century BC and archaeological evidence suggest that its use continued throughout the Roman period (Rothaus, 1995; Stiros et al., 1996). Lechaion harbor site lies in the southern coastal area of the Lechaion Gulf (Fig. 1). The broader area comprises alluvial and coastal deposits including loose materials, sands, pebbles and gravels (Papanikolaou et al., 1998).